Anti-tumor Synergistic Effect of a Dual Cancer-Specific Recombinant Adenovirus and Paclitaxel on Breast Cancer - Wang, Jing; Li, Yiquan; Li, Shanzhi; Yao, Wei; Liu, Xing; Zhu, Yilong; Li, Wenjie; Sun, Liankun; Jin, Ningyi; Li, Xiao (Frontiers in Oncology, 2020)
This study aimed at investigating the anticancer potential of the recombinant adenovirus Ad-apoptin-hTERTp-E1a (Ad-VT) and its synergistic combination with paclitaxel (PTX) in breast cancer treatment. First, we used the Calcusyn software to analyze the synergy between the Ad-VT and paclitaxel, and to determine the final drug concentration. Second, we used crystal violet staining and WST-1 assays to analyze the inhibitory effect of Ad-VT and paclitaxel combination treatment on MCF-7, MDA-MB-231, and MCF-10A cells. Subsequently, we used Hoechst, Annexin V, JC-1 staining to analyze the inhibition pathway of drugs on breast cancer cells. We also used Transwell assays to analyze the cell migration and invasion of MCF-7 and MDA-MB-231 cells. The pGL4.51 plasmid was used to transfect and to generate MDA-MB-231 cells, that stably express luciferase (MDA-MB-231-LUC). The in vivo tumor inhibition effect of Ad-VT and paclitaxel combination treatment was subsequently confirmed using a tumor-bearing nude mouse model. This combination treatment can increase the inhibition of breast cancer cells and reduce paclitaxel toxicity. Ad-VT had a strong apoptosis-inducing effect on MCF-7 and MDA-MB-231 cells, that was mainly mediated through the mitochondrial apoptotic pathway. The combination of Ad-VT and paclitaxel could significantly increase the inhibition of breast cancer cell migration and invasion. Combination of Ad-VT and paclitaxel can inhibit tumor growth and reduce toxicity in vivo. Ad-VT can also inhibit the growth of breast cancer cells and promote their apoptosis. Meanwhile, when it is combined with paclitaxel, Ad-VT could play a significant role in a synergistic tumor inhibition.